PENGARUH BANKING SERVICE QUALITY (BSQ) TERHADAP KEPUASAN DAN LOYALITAS NASABAH PADA PT. BANK MANDIRI (PERSERO) TBK CABANG SUNGGUMINASA - Nur Riyana Putri; Syamsu Alam; Abdullah Sanusi (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
This study aims to know and analyze the Banking Quality Service (BSQ) to customer satisfaction and loyalty PT. Bank Mandiri (Persero) TBK Branch Sungguminasa. The population of this study as many as 12,356 customers in 2017. While the sample research of 100 people using the technique of Accidental sampling. Hypothesis testing was performed using partial least square data analysis (PLS) processed using Smart PLS 2.0. Dependent variable, namely banking service quality (BSQ) with effectiveness and assurance indicators, access, price embodiment, service portfolio, and reliability. While the independent variable consists of customer satisfaction (with indicator of form, reliability, responsiveness, assurance, empathy) and customer loyalty (with indicators of transaction habits, repeat transactions, recommendations, commitments).The results of the analysis of the banking service quality, satisfaction, and loyalty of customers obtained the findings empirically that satisfaction can mediate the influence of banking service quality on customer loyalty in a positive and significant. Where better banking service quality PT. Bank Mandiri (Persero) Tbk Sungguminasa Branch will increase customer satisfaction so that it can also increase loyalty.